Heart Dosimetric Parameters Were Associated With Cardiac Events and Overall Survival for Patients With Locally Advanced Esophageal Cancer Receiving Definitive Radiotherapy - Cai, Guoxin; Li, Chuanbao; Yu, Jinming; Meng, Xue (Frontiers in Oncology, 2020)
Objectives: The aim of this study was to assess the association between heart dosimetric parameters and cardiac events or overall survival (OS) for patients with stage III esophageal cancer receiving definitive radiotherapy. Materials and Methods: Patients with stage III esophageal cancer receiving definitive radiotherapy at our hospital from 2011 to 2013 were enrolled retrospectively. The primary endpoint was grade ≥ 2 cardiac events, and the second endpoint was 5-year OS. Competing risk analysis and Cox regressions analysis were performed to evaluate the association between heart dose and cardiac events or OS. Results: Three hundred forty-six patients were analyzed. Median follow-up was 30 months. Median prescribed dose was 60 Gy. Seventy-eight patients (22.5%) had 91 grade ≥ 2 cardiac events, at a median of 14 months to first event. Thirty-three patients (9.5%) had 42 grade ≥ 3 cardiac events. Of the 78 patients with grade ≥ 2 cardiac events, 70 (89.7%) had the first cardiac events that occurred within first 3 years after radiotherapy. Multivariable analysis showed that preexisting ischemic heart disease [hazard ratio (HR), 2.26; 95% confidence interval (CI), 1.26–4.06; p = 0.006] and mean heart dose (HR, 1.12; 95% CI, 1.04–1.20; p = 0.002) were significantly associated with increased risk of grade ≥ 2 cardiac events. Disease progression (HR, 2.60; 95% CI, 1.82–3.70; p < 0.001), Eastern Cooperative Oncology Group (ECOG) performance status (HR, 0.71; 95% CI, 0.56–0.91; p = 0.007), heart volume receiving ≥ 5 Gy (V5, HR, 1.01; 95% CI, 1.00–1.03; p = 0.035), and gross tumor volume (GTV; HR, 1.00; 95% CI, 1.00–1.00; p = 0.020) were significant predictors of 5-year OS on multivariable analysis. Conclusion: Higher heart dose was significantly associated with an increased cardiac event rate and a worse OS outcome for patients with stage III esophageal cancer treated with definitive radiotherapy. Most of the first cardiac events occurred within first 3 years after treatment.